2004
DOI: 10.1177/147323000403200509
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bupivacaine and Neostigmine on Articular Cartilage and Synovium in the Rabbit Knee Joint

Abstract: We investigated the effects of intra-articular injections of bupivacaine and neostigmine on articular cartilage and the synovial membrane of rabbit knee joints. Saline, bupivacaine or neostigmine were each administered intra-articularly into 15 knee joints. Five joints per drug treatment were prepared for histopathological examination 24 h, 48 h and 10 days after injection. A pathologist examined the histological samples for inflammation of the articular cartilage, inflammatory cell infiltration, hypertrophy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 19 publications
2
59
0
Order By: Relevance
“…They concluded that the acute inhibition caused by bupivacaine is normalised by day three following injection, and hence could be used safely for intraarticular analgesia. The potentially harmful effects of bupivacaine on articular cartilage were first reported by Dogan et al, 11 who injected saline or 0.5% bupivacaine into rabbit knee joints and examined cartilage specimens histopathologically after 24 h, 48 h or 10 days. They found that the specimens from animals receiving bupivacaine showed significantly more inflammatory changes in the form of inflammatory cell infiltration and synovial membrane cell hyperplasia and hypertrophy compared to saline control.…”
Section: 2mentioning
confidence: 99%
“…They concluded that the acute inhibition caused by bupivacaine is normalised by day three following injection, and hence could be used safely for intraarticular analgesia. The potentially harmful effects of bupivacaine on articular cartilage were first reported by Dogan et al, 11 who injected saline or 0.5% bupivacaine into rabbit knee joints and examined cartilage specimens histopathologically after 24 h, 48 h or 10 days. They found that the specimens from animals receiving bupivacaine showed significantly more inflammatory changes in the form of inflammatory cell infiltration and synovial membrane cell hyperplasia and hypertrophy compared to saline control.…”
Section: 2mentioning
confidence: 99%
“…However, there is one study where neostigmine was applied as analgesic agent intra-articularly to the rabbit knee joint, leading to increased infiltration of immune cells, cell hyperplasia and hypertrophy [207]. Also here, mode and time point of application may be relevant for the effects observed.…”
Section: Musculoskeletal Systemmentioning
confidence: 99%
“…Although findings were more severe with neostigmine treatment, bupivacaine injection also caused more increased inflammation, inflammatory cell infiltration, synovial hyperplasia, and hypertrophy than saline in joint cartilage and the synovium (19). Gomoll et al (20) developed an empirical model using 30 rabbits divided into 3 groups treated with saline as a continuous infusion, bupivacaine as a continuous infusion, or bupivacaine and epinephrine as a continuous infusion into shoulder joints for 48 h. When osteochondral and synovial samples from the glenohumeral joint were examined by measuring metabolic sulfate acquisition after 1 week, sulfate was decreased by 50% and 56%, respectively, in bupivacaine and bupivacaine and epinephrine continuous-infusion groups compared with the saline continuous-infusion group.…”
Section: Discussionmentioning
confidence: 99%